Comparison of frequency of vaginal delivery with cesarean section and its causes in Shahroud (2000) - N Bolbol Haghighi; H Ebrahimi; ME Ajami (JRI, 2002)
Cesarean is performed as a routine surgery nowadays and not only many facilities, hospital beds and equipments and professional personnel are involved but also mortality rate and pregnancy complications are more common in women who have undergone cesarean than those who have vaginal deliveries. The aim of this study was to evaluate and compare the frequency of vaginal delivery, cesarean and its causes in Shahroud, so that finding would be used for proper planning to promote vaginal delivery. This is a cross-sectional study. Data gathering instruments are two questionnaires, which were prepared base on objectives of research. When their validity was determined, necessary information was gathered in 5 months. Results showed that total number of delivery in Shahroud were 1221 cases which 1.3% of deliveries were with vaccum 42.1% cesarean and 56.6% vaginal deliveries at this period. The most common causes of cesarean were previous history of cesarean (26.1%) willing to perform tubectomy (9.5%) and cephalopelvic disproportion (8.4%). Cesarean frequency in Shahroud is higher than accepted international statistics (20-22%). Considering that the most common cause of cesarean is history of previous cesarean and since many researches believe that vaginal delivery is safe after cesarean, we hope this outbreak of cesarean rate decreases in this town and consequently all over the country by public training to promote vaginal delivery.
Keywords: Cesarean section, Vaginal delivery, Vaccum, Mothers health